How To Teach Your Baby To Be Physically Superb - Glenn Doman, Douglas Doman & Bruce Hagy
The early development of mobility in newborns is a vital part of their future ability to learn and grow to full potential. How To Teach Your Baby To Be Physically Superb was designed to help you maximize your child$1 (Bs physical capabilities. The authors clearly explain each stage of mobility and show how to create an environment that will enable your baby to more easily achieve that stage. Full-color charts, photographs, illustrations, and detailed easy-to-follow instructions guide you in creating an effective home program.s